The Role of Factor V Leiden, Prothrombin G20210A, and MTHFR C677T Mutations in Neonatal Cerebral Sinovenous Thrombosis - Garrido-Barbero, Maria (Clin Appl Thromb Hemost, 2019)
Little is known about the pathogenesis of cerebral sinovenous thrombosis (CSVT) in the neonate. Although thrombophilia has been described as increasing the risk of CSVT in adults, it remains controversial in pediatric patients, and prospective case–control studies regarding neonatal CSVT are lacking. From 2008 to 2017, all 26 consecutive newborn infants ≥35 weeks of gestation diagnosed with neonatal CSVT, and their mothers, were tested for factor V Leiden (FV) G1691A, FII G20210A, and methylenetetrahydrofolate reductase C677T (MTHFR C677T) mutations. Eighty-five mother–infant pairs were recruited as controls. All infants except 1 with CSVT were suspected due to clinical symptoms, mainly seizures (22/25). Magnetic resonance imaging was performed in 24/26 infants. Heterozygous FV G1691A, FII G20210A, and homozygous MTHFR C677T mutations were present in 1/26, 3/26, and 3/20 infants with CSVT, respectively. FII (odds ratio: 10.96; 95% confidence interval [CI]: 1.09-110.35) and male sex (3.93; 95% CI: 1.43-10.76) were associated with CSVT. When FII G20210A analysis was adjusted for sex, the OR for FII G20210A was 6.70 (95% CI: 0.65-69.22). No differences were found for FV G1691A or homozygous MTHFR mutations between neonates with CSVT and their mothers, compared to controls.